2018
DOI: 10.1103/physrevx.8.031083
|View full text |Cite
|
Sign up to set email alerts
|

Kerker Effect in Ultrahigh-Field Magnetic Resonance Imaging

Abstract: Ultrahigh-field (UHF) magnetic resonance imaging (MRI) systems are getting a lot of attention as they ensure high intrinsic signal-to-noise ratio resulting in higher spatial and temporal resolutions as well as better contrast. This promises improved clinical results with regard to morphological as well as functional and metabolic capabilities. Traditionally, MRI relies on volume coils (birdcage) able to deliver a homogeneous radio frequency field exciting the nuclei magnetic spin. However, this strategy is hin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 33 publications
0
28
0
Order By: Relevance
“…The ability of metamaterials to manipulate the magnetic field has enabled their applications to inductive wireless power transfer, [18] enhancement of the magneto-optic effect, [19] high-quality sensing, [20,21] plasmonic perfect absorption, [22] and magnetic field confinement, [23,24] among others. [27] Recently, judiciously designed metamaterials, consisting of wire [28] or helical resonator arrays, [29] have been utilized to enhance the signal-to-noise ratio (SNR) of the MRI by amplifying the radio-frequency (RF) magnetic field strength due to their capacity for magnetic field enhancement. For example, negative permeability metamaterials have been employed as waveguides [25] and lenses [26] to image deep tissues using 1.5 Tesla (T) MRI systems and a cylindrical meta-atom has been developed to mitigate the field inhomogeneity in 7 T MRI systems based on the Kerker effect.…”
mentioning
confidence: 99%
“…The ability of metamaterials to manipulate the magnetic field has enabled their applications to inductive wireless power transfer, [18] enhancement of the magneto-optic effect, [19] high-quality sensing, [20,21] plasmonic perfect absorption, [22] and magnetic field confinement, [23,24] among others. [27] Recently, judiciously designed metamaterials, consisting of wire [28] or helical resonator arrays, [29] have been utilized to enhance the signal-to-noise ratio (SNR) of the MRI by amplifying the radio-frequency (RF) magnetic field strength due to their capacity for magnetic field enhancement. For example, negative permeability metamaterials have been employed as waveguides [25] and lenses [26] to image deep tissues using 1.5 Tesla (T) MRI systems and a cylindrical meta-atom has been developed to mitigate the field inhomogeneity in 7 T MRI systems based on the Kerker effect.…”
mentioning
confidence: 99%
“…In this configuration the HMA is deported between the emission coil and the receive array in order to maintain the patient's comfort. We demonstrated analytically using the impedance matrix [6], numerically and with measurement that the HMA structure is perfectly compatible with a birdcage emitter and does not perturb the receive array. Moreover, it has the ability to enhance both transmit and receive signal with the possibility to fill gaps usually observed in the brain temporal lobes.…”
Section: Marc Duboismentioning
confidence: 96%
“…Common formulations of dielectric pads for 7T applications are based on BaTiO3 mixed with water present some drawbacks such as performance decay over time. While previous studies tackled directly the formulation problem introducing new dielectric materials and solvent [5], we adopted a new approach based on metamaterial [6]. We demonstrated that the hybridization of four parallel metallic wires arranged on a square unit cell provides the ability to control radiofrequency field inside a 7T head birdcage.In the first part of this work, we show that these hybridized meta-atom (HMA) can be used like a dielectric pad placed on the side of the patient's head.…”
mentioning
confidence: 99%
“…Earlier works based on metamaterials aimed to bring more flexibility on this trade-off by attempting to control the sensitive volume and the SNR independently [6][7][8]. These configurations were based on coupled-wire arrays and relied on the hybridization mechanism [9]. The wires were either of a resonant length [9] or miniaturized using high permittivity materials [10] or capacitive interconnections [11].…”
Section: Introductionmentioning
confidence: 99%